Mucosal-associated invariant T cell alterations during the development of human type 1 diabetes - Ahmad Mahfuz, Gazali; Schroderus, Anna-Mari; Salonen, Kirsti Näntö; Rintamäki, Reeta; Pihlajamäki, Jussi; Knip, Mikael; Veijola, Riitta; Toppari, Jorma; Ilonen, Jorma; Kinnunen, Tuure (Springer, 2020)
Aims/hypothesis Mucosal-associated invariant T (MAIT) cells are innate-like T cells that recognise derivatives of bacterial riboflavin metabolites presented by MHC-Ib-related protein 1 (MR1) molecules and are important effector cells for mucosal immunity. Their development can be influenced by the intestinalmicrobiome. Since the development of type 1 diabetes has been associated with changes in the gut microbiome, this can be hypothesised to lead to alterations in circulating MAIT cells. Accordingly, peripheral blood MAIT cell alterations have been reported previously in patients with type 1 diabetes. However, a comprehensive analysis of the frequency and phenotype of circulating MAIT cells at different stages of type 1 diabetes progression is currently lacking. Methods We analysed the frequency, phenotype and functionality of peripheral bloodMAIT cells, as well as γδ T cells, invariant natural killer T (iNKT) cells and natural killer (NK) cells with flow cytometry in a cross-sectional paediatric cohort (aged 2–15) consisting of 51 children with newly diagnosed type 1 diabetes, 27 autoantibody-positive (AAb+) at-risk children, and 113 healthy control children of similar age and HLA class II background. The frequency ofMAIT cells was also assessed in a separate crosssectional adult cohort (aged 19–39) of 33 adults with established type 1 diabetes and 37 healthy individuals of similar age. Results Children with newly diagnosed type 1 diabetes displayed a proportional increase of CD8−CD27− MAIT cells compared with healthy control children (median 4.6% vs 3.1% ofMAIT cells, respectively, p = 0.004), which was associated with reduced expression of C-C chemokine receptor (CCR)5 (median 90.0% vs 94.3% of MAIT cells, p = 0.02) and β7 integrin (median 73.5% vs 81.7% of MAIT cells, p = 0.004), as well as decreased production of IFN-γ (median 57.1% vs 69.3% of MAIT cells,